1975
DOI: 10.1111/j.2042-3306.1975.tb03222.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation and Cardiovascular Studies during Mechanical Control of Ventilation in Horses

Abstract: SUMMARY Eleven out of 12 horses were underventilating while breathing spontaneously during halothane anaesthesia with high arterial carbon dioxide tensions. In addition, large alveolar to arterial oxygen tension gradients were found to be present. Mechanically, controlled ventilation with an intermittent positive pressure of 20–30 cm H2O reduced arterial carbon dioxide levels to normal. The alveolar to arterial oxygen gradients did not increase and in some cases decreased. These (A − a) Po2 gradients were due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…This is in line with reports (Weaver and Walley 1975;Whitehair and Willits 1999) which suggest that the use of intermittent positive pressure ventilation does not always improves PaO 2 but may even decrease it. It is thought that over-inflating the compliant upper alveoli (with high V/Q) which are less subject to abdominal counter pressure not only increases vascular resistance in this zone but also leads to additional compression of dependent alveoli.…”
Section: Discussionsupporting
confidence: 80%
“…This is in line with reports (Weaver and Walley 1975;Whitehair and Willits 1999) which suggest that the use of intermittent positive pressure ventilation does not always improves PaO 2 but may even decrease it. It is thought that over-inflating the compliant upper alveoli (with high V/Q) which are less subject to abdominal counter pressure not only increases vascular resistance in this zone but also leads to additional compression of dependent alveoli.…”
Section: Discussionsupporting
confidence: 80%
“…In horses, as in other species, IPPV strongly interferes with cardiovascular function. 36,40,41 There are marked additional depressing effects on cardiovascular parameters when IPPV is combined with PEEP, 37,38,42 decreasing CO by as much as 50%. 39 The purpose of the study reported here was to evaluate pulmonary and cardiovascular effects of an RM combined with PEEP during TIVA in ponies.…”
mentioning
confidence: 97%
“…Pulmonary shunting in anesthetized horses reportedly increases by 21% to 51% (mean, 34%), compared with 4% to 7% in standing horses prior to anesthesia. 11,a Furthermore, administration of a high concentration of inspired oxygen (> 95%) during anesthesia in horses has been associated with an increase in intrapulmonary shunting and a decrease in gas exchange. 6 Airway closure and atelectasis formation in humans can be responsible for as much as 74% of gas exchange impairment.…”
mentioning
confidence: 99%